First-Year Seminar Course List: Spring 2016 - Kansas State University, K-State First (Kansas State University. K-State First., 2016)
Course Listings for first-year seminar classes (FYS) for the 2016 spring semester. The academic content of FYS classes is the same as other sections of the same course, but enrollment is limited to first-year students in sections of 22 or fewer. FYS classes emphasize communication, critical thinking, and community building. Students benefit from a learning environment built around engagement, interaction, and application of concepts. All classes count as a K-State 8, general education class.
Keywords: First-year seminars; Course list; K-State 8; Spring 2016; Enrollment; General Education; Fliers (printed matter)